A new two‐dimensional cadmium(II) coordination polymer based on Cd6(CHADC)6 clusters (H2CHADC is cyclohexane‐1, 2‐dicarboxylic acid): synthesis, structure and properties. Issue 7 (27th June 2022) - Shen, Hong
Abstract : A cadmium(II) coordination polymer prepared by the reaction of Cd(NO3 )2 ·6H2 O with cis ‐cyclohexane‐1, 2‐dicarboxylic acid and 4, 4′‐bis(2‐methyl‐1 H ‐imidazol‐1‐yl)biphenyl in a mixture of H2 O and dimethylformamide, possesses a 6‐connected hxl two‐dimensional layer based on Cd6 (CHADC)6 clusters with the point symbol (3 6 ·4 6 ·5 3 ). The coordination polymer displays a highly selective and sensitive sensing for Fe 3+ cations and Cr2 O7 2− /CrO4 2− anions through luminescence quenching effects in aqueous solutions. Abstract : The highly effective recognition and detection of metal ions and anions in water has attracted much attention with respect to environmental safety. Herein, a novel Cd‐based coordination polymer, poly[[4, 4′‐bis(2‐methylimidazol‐1‐yl)biphenyl]bis(cyclohexane‐1, 2‐dicarboxylato)dicadmium(II)], [Cd2 (C8 H10 O4 )2 (C20 H18 N4 )] n or [Cd(CHADC)(4, 4′‐BMIBP)0.5 ] n, (I), has been synthesized employing cis ‐cyclohexane‐1, 2‐dicarboxylic acid (H2 CHADC) and 4, 4′‐bis(2‐methyl‐1 H ‐imidazol‐1‐yl)biphenyl (4, 4′‐BMIBP). Single‐crystal X‐ray analysis reveals that (I) presents a 6‐connected hxl two‐dimensional layer based on Cd6 (CHADC)6 clusters with the point symbol (3 6 ·4 6 ·5 3 ). Furthermore, (I) has been characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis and fluorescence spectroscopy, and exhibits good stability and excellent photoluminescence properties. Coordination polymer (I) was chosen as a fluorescent probe to sense different target analytes and shows an obvious selective recognition response to Fe 3+ cations and Cr2 O7 2− /CrO4 2− anions through luminescence‐quenching effects in aqueous solution. The sensing mechanism was investigated and showed that the detection mechanism was resonance energy transfer between (I) and the Fe 3+, Cr2 O7 2− and CrO4 2− ions.